An experimental study on the vibration behavior and the physical properties of weft-knitted spacer fabrics manufactured using flat knitting technology. Issue 3 (February 2023) - Chen, Fuxing; Wang, Ji; Gao, Shouwu; Ning, Xin; Yan, Pengxiang; Tian, Mingwei
Weft-knitted spacer fabrics, a kind of three-dimensional fabric structure, are potential substitutes for typical rubber sponges and polyurethane foams for the protection of human body from exposure to vibrations. To explore the capability and the designability of weft-knitted spacer fabrics as the functional material of personal protective equipment against vibration, such as anti-vibration gloves and car cushions, the vibration behavior and physical properties of weft-knitted spacer fabrics manufactured using flat knitting technology were studied. In the first part of the article, the vibration behavior of top-loaded weft-knitted spacer fabric under harmonic base excitation was analyzed. The effects of monofilament diameter, linking distance and excitation acceleration level on the transmissibility curve of the mass-spacer fabric were evaluated. It was shown that to broaden the frequency range for vibration isolation, spacer fabrics with smaller monofilament diameter and longer linking distance were preferred. In the second part of the article, the effects of monofilament type, monofilament diameter, and spacer structure on the physical properties of spacer fabric including fabric shrinkage coefficient, fabric thickness, fabric stitch densities, and fabric areal mass were analyzed. It was found that fabric thickness was increased by employing spacer structures with longer linking distance and lower filling density of spacer monofilament. In addition, in order to obtain an optimized high fabric thickness, nylon monofilament was preferred to polyester monofilament. On the other hand, monofilament diameter has a significant influence on stitch densities and fabric areal mass. Larger monofilament diameter resulted in lower stitch densities and heavier areal mass for spacer fabric.